Ґенезис трансформації економіки на основі цифрової ігрової індустрії - Чизмар Іван; Chyzmar Ivan; Csizmár Iván (ТОВ «ДКС Центр», 2020)
Резюме. Метою дослідження є опис особливостей походження, виникнення, становлення, розвитку економіки на основі цифрової ігрової індустрії. Мета обумовила постанову таких завдань дослідження: 1) характеристика впливу цифрової ігрової індустрії на світову економіку; 2) розгляд специфіки посилення впливу цифрової ігрової індустрії на світову економіку у розрізі етапів її становлення; 3) виділення основних подій щодо кожного етапу, що викликали трансформації економіки. Результати дослідження дозволили констатувати, що цифрова ігрова індустрія сформувала відокремлений сектор економіки. Цей сектор узагальнює галузі з подібними загальними характеристиками, щодо особливостей господарської діяльності, пов'язаної з; розробкою; просуванням; продажем комп'ютерних ігор; унікальним ланцюжком цінності. Окреслений сектор характеризувався не тільки особливостями походження, виникнення, становлення, але і поступовим посиленням впливу на економіку (через його ендеміки). Зміст трансформацій простежується від процесу первинного зародження уявлень про віртуальний продукт привабливий для споживачів до формування ринку із необмеженими віртуальними потребами споживачів і пропозицією виробників. Перспективи подальших розвідок у даному напрямі полягають у дослідженні впливу на економіку ендемічних секторів цифрової ігрової індустрії.

Abstract. The video game industry since the mid-1970s from a small market with the mainstream has evolved to the economic sector associated with the development, promotion, and sale of video games. This evolution was part of the global transformation of the industrial society into an information society, as well as the virtualization of the social reproduction system, which affected most processes of production, distribution, exchange, and consumption of goods and services. The economy was changing in the processes of social reproduction, where real-life products were emerging and improving. The digital gaming industry has developed its value chain and has material and intellectual social utility at interrelated levels. The aim of the research is to describe the characteristics of origin, emergence, development of an economy based on the digital gaming industry. The objective defined such research objectives: сharacterization of the economic impact of the digital gaming industry; defining the specifics of strengthening the impact of the digital gaming industry on the economy in its formative stages; highlighting the main developments in each stage that led to the transformation of the economy. The results of the study showed that the digital gaming industry had formed a separate industry. This sector of the economy combines areas with similar characteristics of the actual activities associated with the development, promotion, and sale of video games and a unique value chain. The sector was characterized by unique characteristics of origin and development, as well as a gradual increase in the impact on the economy through its endemic features (including cybersport; gamedev; virtual reality, and augmented reality). Digital gaming industry endemic to specific elements of game development, promotion, and sales that synthesize transformations in the quality of economies. Transformations can be traced from the process of the initial conception of a virtual product to the formation of a market with unlimited virtual consumer needs and producer supply. The prospects for further research in this area lie in the endemic sectors of the digital gaming industry.
The genesis of economic transformation through the digital gaming industry
Редакційна колегія: http://www.economy.nayka.com.ua/?op=7
Зміст: http://www.economy.nayka.com.ua/?n=11&y=2020
Keywords: сектор економіки; цифрова ігрова індустрія; ендемічні сектори; ланцюжок цінності; economic sector; digital gaming industry; endemic sectors; value chain